Activity of methylgerambullin from Glycosmis species (Rutaceae) against Entamoeba histolytica and Giardia duodenalis in vitro. (August 2019) - Drinić, Mirjana; Raninger, Adriane; Zraunig, Andrea; Astelbauer, Florian; Leitsch, David; Obwaller, Andreas; Walochnik, Julia; Greger, Harald; Duchene, Michael
Abstract: Entamoeba histolytica and Giardia duodenalis are widespread intestinal protozoan parasites which both spread via cysts that have to be ingested to infect a new host. Their environment, the small intestine for G. duodenalis and the colon for E. histolytica, contains only very limited amounts of oxygen, so both parasites generate energy by fermentation and substrate level phosphorylation rather than by oxidative phosphorylation. They both contain reducing agents able to reduce and activate nitroimidazole drugs such as metronidazole which is the gold standard drug to treat Entamoeba or Giardia infections. Although metronidazole works well in the majority of cases, it has a number of drawbacks. In animal models, the drug has carcinogenic activity, and concerns about a possible teratogenic activity remain. In addition, the treatment of G. duodenalis infections is hampered by emerging metronidazole resistance. Plant-derived drugs play a dominant role in human medicine, therefore we tested the activity of 14 isolated plant compounds belonging to seven different classes in vitro against both parasites. The tests were performed in a new setting in microtiter plates under anaerobic conditions. The compound with the highest activity was methylgerambullin, a sulphur-containing amide found in Glycosmis species of the family Rutaceae with an EC50 of 14.5 μM (6.08 μg/ml) after 24 h treatment for E. histolytica and 14.6 μM (6.14 μg/ml) for G. duodenalis . The compound was successfully synthesised in the laboratory which opens the door for the generation of new derivatives with higher activity. Graphical abstract: Image 1 Highlights: Fourteen plant compounds of seven classes were isolated. The activity against Entamoeba histolytica and Giardia duodenalis was tested. Methylgerambullin had the highest activity against both parasites. Methylgerambullin is a sulphur-containing amide from Glycosmis spp. ( Citrus plants). High cysteine concentrations interfered with methylgerambullin activity.